Aluminum alloy foil and manufacturing method of the same

By optimizing the composition and microstructure of aluminum alloy foils, specifically through controlling the Fe and Si content and the grain orientation, the challenges of achieving high moldability and suppressing surface roughness are addressed, resulting in improved mechanical properties and productivity.

JP2025062590AActive Publication Date: 2025-04-14MA ALUMINUM CORP

Patent Information

Application Number
JP2024173331
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-10-02
Publication Date
2025-04-14
Estimated Expiration
2043-10-02

Smart Images

  • Figure 2025062590000001_ABST
    Figure 2025062590000001_ABST
Patent Text Reader

Abstract

To provide an aluminum alloy foil.SOLUTION: An aluminum alloy foil formed of an aluminum alloy comprising a composition which contains Fe: 0.8 mass% or more and 2.0 mass% or less, and Si: 0.2 mass% or less, and a balance Al and inevitable impurities is such that: 0.2%-yield-strength is 45 MPa or more, and extension is 15% or more; a ratio of an area ratio (Cu orientation / Cube orientation) of Cu orientation to an area ratio of Cube orientation in an area ratio of each orientation on the surface is 3 or more; an average crystal grain size of crystal grains surrounded by an orientation difference of 5° or more is 3.5 μm or less on the surface; and a ratio of crystal grain boundary lengths in the same visual field acquired by performing crystal orientation analysis by an EBSD method on the surface satisfies the following (1) formula. A crystal grain boundary length of crystal grains having an orientation difference of 2° or more and less than 15° / a crystal grain boundary length of crystal grains having an orientation difference of 15° or more>0.5...(1) formula.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aluminum alloy foil and a method for producing the same. [Background technology]

[0002] Aluminum alloy foils used as packaging materials for food products, lithium ion batteries, and the like are required to have high elongation because they are subjected to large deformation during forming such as press forming.

[0003] For example, the following Patent Document 1 discloses a method for producing an aluminum foil having excellent formability, which is made of an aluminum alloy containing 0.7 to 2.0% Fe. The technology described in Patent Document 1 describes a technology in which after hot rolling, the foil is subjected to intensive working at a working rate of 97% or more without intermediate annealing during the cold rolling process until it is a foil product, and then finish annealing is performed at 300 to 450°C. In addition, the following Patent Document 2 describes an aluminum alloy soft foil containing 0.7 to 1.4 mass % Fe, in which the average crystal grain size of crystal grains with a tilt angle exceeding 5° is 3.5 μm or less. The technology described in Patent Document 2 describes a technology for producing a soft foil exhibiting excellent strength by homogenizing an ingot at 400 to 500°C, hot rolling with a hot rolling finish temperature of 300°C or higher, cold rolling without intermediate annealing, and final annealing at 220 to 275°C. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 2-080541 [Patent Document 2] JP 2017-160509 A Summary of the Invention [Problem to be solved by the invention]

[0005] When producing this type of aluminum alloy foil for packaging material, an ingot is obtained by casting a molten alloy having a required composition, and the ingot is subjected to a homogenization treatment, followed by hot rolling and cold rolling, and finally annealing to obtain a packaging material having the desired mechanical properties. Regarding the packaging material produced through such processes, in view of the above-mentioned background, the present inventors have been conducting research and development into aluminum alloy foils suitable as packaging materials such as exterior foils for batteries.

[0006] Based on this research, the present inventors believe that in order to obtain an aluminum alloy foil having high formability, it is important to be able to suppress surface roughness during deformation. In addition, as a result of the inventor's research into aluminum alloy foil for packaging materials, it was found that with regard to surface roughness during deformation, the ratio of the area rate of Cu orientation to the area rate of Cube orientation in the crystal grain structure of the packaging material is important.

[0007] Therefore, the present inventors have reviewed the manufacturing method and examined the crystal structure of aluminum alloy foil for packaging material, with the aim of providing an aluminum alloy foil which can improve productivity and has excellent formability. [Means for solving the problem]

[0008] "1" The aluminum alloy foil of this embodiment is an aluminum alloy foil made of an aluminum alloy containing 0.8% by mass or more and 2.0% by mass or less of Fe, 0.2% by mass or less of Si, with the remainder being Al and unavoidable impurities, and is characterized in that it has a 0.2% yield strength of 45 MPa or more, an elongation of 15% or more, a ratio of the area ratio of Cu orientation to the area ratio of Cube orientation in the area ratio of each orientation on the surface (Cu orientation / Cube orientation) of 3 or more, an average crystal grain size of crystal grains surrounded by an orientation difference of 5° or more on the surface is 3.5 μm or less, and a ratio of crystal grain boundary lengths in the same field of view on the surface obtained by performing crystal orientation analysis using the EBSD method satisfies the following formula (1). Length of grain boundary of crystal grains with misorientation of 2° or more and less than 15° / Length of grain boundary of crystal grains with misorientation of 15° or more > 0.5... (1)

[0009] [2] In the aluminum alloy foil according to [1] of the present embodiment, instead of the formula (1), it is preferable that the ratio of grain boundary lengths in the same field of view obtained by performing crystal orientation analysis by EBSD method on the surface satisfies the following formula (2): 0.52≦grain boundary length of crystal grains with orientation difference of 2° or more and less than 15° / grain boundary length of crystal grains with orientation difference of 15° or more≦0.88…(2) [3] In the aluminum alloy foil according to [1] or [2] of this embodiment, the initial surface roughness Ra0 and the surface roughness Ra at a strain of 25% in a tensile test are 25 The difference between the surface roughness (Ra 25 -Ra0) is preferably 0.30 μm or less.

[0010] "4" The aluminum alloy foil of this embodiment is an aluminum alloy foil made of an aluminum alloy having a composition containing Fe: 0.8% by mass or more and 2.0% by mass or less, Si: 0.2% by mass or less, with the remainder being Al and unavoidable impurities, and has a 0.2% yield strength of 45 MPa or more, an elongation of 15% or more, a ratio of the area ratio of Cu orientation to the area ratio of Cube orientation in the area ratio of each orientation on the surface (Cu orientation / Cube orientation) of 3 or more, an average crystal grain size of crystal grains surrounded by an orientation difference of 5° or more on the surface is 3.5 μm or less, and an initial surface roughness Ra0 and a surface roughness Ra at a strain of 25% in a tensile test are 25 The difference between the surface roughness (Ra 25 -Ra0) is 0.30 μm or less. [5] In the aluminum alloy foil according to [4] of the present embodiment, the surface roughness (Ra 25 -Ra0) is preferably 0.17 μm or more and 0.29 μm or less.

[0011] "6" A method for producing an aluminum alloy foil according to the present embodiment is an aluminum alloy foil made of an aluminum alloy containing 0.8% by mass or more and 2.0% by mass or less of Fe, 0.2% by mass or less of Si, with the remainder being Al and unavoidable impurities, characterized in that the aluminum alloy foil has a 0.2% proof stress of 45 MPa or more, an elongation of 15% or more, a ratio of the area rate of Cu orientation to the area rate of Cube orientation in the area rate of each orientation on the surface (Cu orientation / Cube orientation) of 3 or more, an average crystal grain size of crystal grains surrounded by an orientation difference of 5° or more on the surface of 3.5 μm or less, and a ratio of grain boundary lengths in the same field of view on the surface obtained by performing crystal orientation analysis by the EBSD method satisfies the following formula (1): The method is characterized in that an ingot of an aluminum alloy having the above composition is subjected to a homogenization treatment in which it is heated and held at 480 to 540°C for 8 hours or more and then cooled, and then is hot-rolled to a finishing temperature of 240°C to 300°C, and then is cold-rolled to a rolling ratio of 98% or more, and then is foil-rolled without intermediate annealing, and is finally annealed by heating to 220 to 350°C for 30 minutes to 20 hours. Length of grain boundary of crystal grains with misorientation of 2° or more and less than 15° / Length of grain boundary of crystal grains with misorientation of 15° or more > 0.5... (1)

[0012] [7] In the method for producing an aluminum alloy foil according to [6] of the present embodiment, it is preferable to produce an aluminum alloy foil in which the ratio of grain boundary lengths in the same field of view, obtained by performing crystal orientation analysis by the EBSD method on the surface, satisfies the following formula (2) instead of the formula (1). 0.52≦grain boundary length of crystal grains with orientation difference of 2° or more and less than 15° / grain boundary length of crystal grains with orientation difference of 15° or more≦0.88…(2) [8] In the method for producing an aluminum alloy foil according to [6] or [7] of the present embodiment, the initial surface roughness Ra0 and the surface roughness Ra at a strain of 25% in a tensile test are 25 The difference between the surface roughness (Ra 25 -Ra0) is preferably 0.30 μm or less.

[0013] "9" A method for producing an aluminum alloy foil according to the present embodiment is an aluminum alloy foil made of an aluminum alloy containing 0.8% by mass or more and 2.0% by mass or less of Fe, 0.2% by mass or less of Si, and the remainder being Al and unavoidable impurities, the aluminum alloy foil having a 0.2% proof stress of 45 MPa or more, an elongation of 15% or more, a ratio of an area rate of Cu orientation to an area rate of Cube orientation in the area rate of each orientation on the surface (Cu orientation / Cube orientation) of 3 or more, an average crystal grain size of crystal grains surrounded by an orientation difference of 5° or more on the surface of 3.5 μm or less, an initial surface roughness Ra0 and a surface roughness Ra at a strain of 25% in a tensile test 25 The difference between the surface roughness (Ra 25 The method for producing an aluminum alloy foil having a surface roughness (R0-Ra0) of 0.30 μm or less comprises the steps of: subjecting an ingot of an aluminum alloy having the above composition to a homogenization treatment in which the ingot is heated and held at 480 to 540°C for 8 hours or more and then cooled; subjecting the ingot to hot rolling with a finishing temperature of 240°C or more and less than 300°C; subjecting the ingot to cold rolling with a rolling reduction rate of 98% or more; thereafter, rolling the ingot into a foil without intermediate annealing; and subjecting the ingot to final annealing in which the ingot is heated to 220 to 350°C for 30 minutes to 20 hours.

[0014] "10" In the method for producing an aluminum alloy foil according to the present invention, 25 It is preferable to produce an aluminum alloy foil having a roughness Ra of 0.17 μm or more and 0.29 μm or less.

[11] In the method for producing an aluminum alloy foil according to any one of [6], [7], [9], and

[10] of the present embodiment, the homogenization treatment is preferably carried out under conditions of heating and holding at 480 to 540°C for 8 hours or more and 16 hours or less, followed by cooling.

[12] In the method for producing an aluminum alloy foil according to [8] of the present embodiment, the homogenization treatment is preferably carried out under conditions of heating and holding at 480 to 540° C. for 8 to 16 hours, followed by cooling. Effect of the Invention

[0015] According to the aluminum alloy foil of the present invention, it is possible to provide an aluminum alloy foil having high formability. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a plan view showing a first embodiment of an aluminum alloy foil according to the present invention. [Diagram 2] FIG. 2 is a diagram showing the planar shape of a square punch used in a limit forming height test in an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, an example of an embodiment of the present invention will be described in detail with reference to the accompanying drawings. Note that the drawings used in the following description may show characteristic parts in an enlarged scale for the sake of convenience in order to make the characteristics easier to understand.

[0018] FIG. 1 is a plan view showing one embodiment of an aluminum alloy foil according to the present invention. The aluminum alloy foil 1 shown in FIG. 1 is a foil obtained by subjecting an ingot obtained by a casting method to hot rolling, cold rolling, and foil rolling, and is depicted in FIG. 1 as a strip having a certain width with its length oriented left and right. The rolling direction of this aluminum alloy foil 1 is the left-right direction (length direction of the strip-shaped foil) shown in Fig. 1, and for convenience, the direction at 0° to the rolling direction means the left-right direction in Fig. 1, the direction at 45° to the rolling direction means the direction of the arrow marked 45° in Fig. 1, and the direction at 90° to the rolling direction means the direction of the arrow marked 90° in Fig. 1. In other words, the direction at 90° to the rolling direction in the aluminum alloy foil 1 means the width direction of the strip-shaped aluminum alloy foil 1 (the vertical direction on the paper in Fig. 1).

[0019] The aluminum alloy foil 1 shown in FIG. 1 is formed to a thickness of, for example, about 0.01 mm to 0.2 mm. The thickness of the aluminum alloy foil 1 may be a general thickness used for foil. For example, it is formed to a thickness of about 0.04 mm (40 μm). In this specification, when "~" is used to indicate a range by describing upper and lower limits, the range includes the upper and lower limits unless otherwise specified. Therefore, 0.01 mm to 0.2 mm means 0.01 mm or more and 0.2 mm or less. The aluminum alloy foil 1 is made of an aluminum alloy containing, for example, 0.8% by mass or more and 2.0% by mass or less of Fe, 0.2% by mass or less of Si, with the remainder being Al and unavoidable impurities.

[0020] As an example, this aluminum alloy foil 1 has a maximum tensile strength of 85 MPa or more, a 0.2% yield strength of 45 MPa or more, and an elongation of 15% or more in a tensile test in a direction at 45° to the rolling direction, and the ratio of the area ratio of Cu orientation to the area ratio of Cube orientation in the area ratios of each orientation on the surface (Cu orientation / Cube orientation) is 3 or more. In the aluminum alloy foil 1, it is preferable that the average crystal grain size surrounded by an orientation difference of 5° or more is 4 μm or less. In the aluminum alloy foil 1, the initial surface roughness Ra0 and the surface roughness Ra at a strain of 25% in a tensile test are 25 The difference between the surface roughness (Ra 25 -Ra0) is preferably 0.30 μm or less. Details of the surface roughness measurement will be explained in the examples described later.

[0021] In the aluminum alloy foil 1, it is preferable that the ratio of grain boundary lengths in the same field of view obtained by performing crystal orientation analysis by the EBSD method satisfies the following formula (1). Length of grain boundary of crystal grains with misorientation of 2° or more and less than 15° / Length of grain boundary of crystal grains with misorientation of 15° or more > 0.5... (1) Furthermore, it is preferable that the aluminum alloy foil 1 has an elongation of 10% or more in both the direction at an angle of 0° and the direction at an angle of 90° to the rolling direction.

[0022] The reasons for limiting the composition, properties, and structure of the aluminum alloy constituting the aluminum alloy foil 1 will be explained below. ·Fe: 0.8 mass% or more and 2.0 mass% or less Fe crystallizes as Al-Fe intermetallic compounds during casting, and if the size of these compounds is appropriate, they become recrystallization sites during annealing, which has the effect of refining the recrystallized grains. If the Fe content is less than 0.8% by mass, the distribution density of the intermetallic compounds will be low, the effect of refining the crystal grains will be low, the final recrystallized grains will be coarse, and the grain boundary density of crystal grains with an orientation difference of 2° or more and less than 15° will be low. If the Fe content exceeds 2.0% by mass, the effect of refining the crystal grains will saturate or decrease, and further the size of the Al-Fe intermetallic compounds generated during casting will become very large, decreasing the elongation, formability, and productivity of the foil. A particularly preferable range for the Fe content is 1.2% by mass or more and 1.8% by mass or less. ·Si: 0.20% by mass or less Si forms intermetallic compounds together with Fe, but excessive addition of Si leads to coarsening of the compound size and a decrease in distribution density. If the content exceeds the upper limit, there is a concern that coarse crystals may cause a decrease in elongation and formability, and furthermore, the uniformity of the recrystallized grain size distribution after final annealing may decrease. For these reasons, the Si content is set to 0.20 mass% or less. For the same reason, it is more preferable to set the upper limit of the Si content to 0.04 mass%.

[0023] The balance of the components constituting the aluminum alloy foil according to the present invention is composed of Al and inevitable impurities. The inevitable impurities refer to elements that are inevitably mixed in during the production of the aluminum alloy foil. The inevitable impurities may be contained within a range that does not affect the properties of the aluminum alloy foil according to the present invention. Examples of the inevitable impurities include elements such as magnesium (Mg), chromium (Cr), manganese (Mn), copper (Cu), zinc (Zn), titanium (Ti), vanadium (V), gallium (Ga), nickel (Ni), boron (B), and zirconium (Zr), and one or more of these may be contained in an amount of 500 mass ppm or less each.

[0024] "In a tensile test at 45° to the rolling direction, the maximum tensile strength is 85 MPa or more, the 0.2% yield strength is 45 MPa or more, and the elongation is 15% or more." The aluminum alloy foil used in packaging materials is subjected to three-dimensional deformation during press forming, and is therefore required to have good mechanical properties not only in the rolling direction but also in various directions. The inventors have found that the mechanical properties in the 45° direction to the rolling direction are particularly important during press forming. In order to maintain the shape during forming and ensure strength after forming, the maximum tensile strength is preferably 85 MPa or more and the 0.2% proof stress is preferably 45 MPa. There is no particular upper limit, but if the maximum tensile strength and the 0.2% proof stress are too high, handling during forming becomes difficult, so more preferably, the maximum tensile strength is 130 MPa or less and the 0.2% proof stress is 85 MPa or less. Elongation is most correlated with formability, and it has been confirmed that in this product, the formability is good when the elongation value in the 45° direction is high. The elongation in the 45° direction to the rolling direction is preferably 15% or more, and most preferably 20% or more.

[0025] "Azimuth area ratio" In the aluminum alloy foil 1, the ratio of the area rate of Cu orientation to the area rate of Cube orientation (Cu orientation area rate / Cube orientation area rate) is preferably 3 or more. (Cu orientation area rate / Cube orientation area rate) can be, for example, 5.0 or more and 31 or less. After electrolytic polishing of the foil surface, crystal orientation analysis can be performed using SEM (Scanning Electron Microscope)-EBSD to calculate the area ratio of each orientation. OIM Analysis by TSL Solutions can be used for the analysis. Deviation from the ideal orientation is limited to 15°. From the obtained area ratio, the ratio of the area ratio of Cu orientation to Cube orientation (Cu orientation area ratio / Cube orientation area ratio) can be calculated. The ideal orientation of each orientation is shown below. The method for calculating the orientation area ratio will be described in detail in the examples. In the aluminum alloy foil of this embodiment, the crystal orientation is aligned in the same direction to suppress surface roughness and improve formability. In the alloy foil of this embodiment, the Cu orientation and the Cube orientation are the main crystal orientations, and the inventors have found that it is important to align the crystal orientation to the Cu orientation. Even if the proportion of the Cu orientation increases, if there is a large amount of Cube orientation, the surface is likely to become rough, which is a factor that deteriorates formability. Therefore, it was decided to index it by the ratio of the area rate of Cu orientation to Cube orientation. As a result of the investigation, it was confirmed that the ratio of the area rate of Cu orientation to Cube orientation (Cu orientation area rate / Cube orientation area rate) is preferably 3 or more, and more preferably 5 or more. If it is less than 3, even if the crystal grains are fine, the surface of the aluminum alloy foil is likely to become rough, and the limit forming height is reduced, resulting in a decrease in formability. Cu orientation {112} <111> Cube direction {001} <100> This ideal direction is expressed as a direction that includes all equivalent directions.

[0026] When the aluminum alloy foil of the present embodiment is plastically deformed, surface roughness (irregularities) occurs on the material surface. The surface roughness is regarded as unevenness in thickness, and by suppressing it, it is possible to prevent a decrease in the limit forming height. The surface roughness Ra0 at the initial stage before plastic deformation and the surface roughness Ra at 25% strain in a tensile test are compared for three-dimensional deformation when used as a packaging material. 25 The difference between the surface roughness (Ra 25 The inventors found that the surface roughness (Ra -Ra0) is important. 25 The surface roughness (Ra -Ra0) is preferably 0.30 μm or less, and more preferably 0.25 μm or less. 25 When Ra0) exceeds 0.30 μm, the limit forming height decreases.

[0027] "The average grain size of grains surrounded by a misorientation of 5° or more is 4.0 μm or less." Soft aluminum foil can suppress the roughness of the foil surface when deformed by making the crystal grains fine, and can be expected to have high elongation and high formability. One of the factors that affect this surface roughness is the crystal grain size. In order to achieve high elongation characteristics and the high formability associated with it, it is desirable that the average crystal grain size is 4.0 μm or less for crystal grains surrounded by grain boundaries with an orientation difference of 5° or more. The present inventors have also found that when the average crystal grain size exceeds 4.0 μm, surface roughness during forming becomes significant, and control of the crystal grain structure is also important for suppressing surface roughness. In the aluminum alloy foil 1, the average crystal grain size is preferably 4.0 μm or less, more preferably 3.5 μm or less. In electron backscatter diffraction (EBSD), a grain boundary map can be obtained by analyzing crystal orientation per unit area, in which crystal grains with an orientation difference of 5° or more are depicted. Details of the method for calculating the average crystal grain size will be described in the examples.

[0028] Length of grain boundary (LAGB) of grains with misorientation between 2° and 15° / length of grain boundary (HAGB) of grains with misorientation of 15° or more>0.5 In order to suppress surface roughness of the aluminum alloy foil, it is considered important that the density of crystal grains with a misorientation of 2° or more and less than 15° is high on the surface of the aluminum alloy foil. Therefore, it is preferable to satisfy the relationship of formula (1), which is: grain boundary length of crystal grains with a misorientation of 2° or more and less than 15° (LAGB) / grain boundary length of crystal grains with a misorientation of 15° or more (HAGB)>0.5. If the relationship is (grain boundary length of crystal grains with orientation misorientation of 2° or more and less than 15°) / (grain boundary length of crystal grains with orientation misorientation of 15° or more)≦0.5, the foil surface will become rough, the limit forming height will be lowered, etc., resulting in reduced formability. More preferably, the grain boundary length of crystal grains with orientation misorientation of 2° or more and less than 15° (LAGB) / grain boundary length of crystal grains with orientation misorientation of 15° or more (HAGB) is >0.6.

[0029] "Method of manufacturing aluminum alloy foil" To manufacture the aluminum alloy foil 1 shown in Fig. 1, a molten aluminum alloy satisfying the above-mentioned composition is prepared, and an aluminum alloy ingot is obtained by a casting method using this molten aluminum alloy. Next, the aluminum alloy ingot is subjected to a homogenization treatment, and processed to a target thickness by hot rolling, cold rolling, and foil rolling, and finally annealed to obtain the aluminum alloy foil 1.

[0030] Homogenization: Maintain temperature at 480-540℃ for 6 hours or more The obtained ingot is preferably subjected to homogenization treatment at 480 to 540°C for 6 hours or more. At temperatures below 480°C, Fe precipitation is small and the growth of intermetallic compounds is insufficient. On the other hand, at temperatures above 540°C, the growth of intermetallic compounds is significant, and the density of fine intermetallic compounds with particle sizes of 0.1 μm or more and less than 1 μm is significantly reduced. For this reason, it is more preferable to select a temperature range of 500 to 540°C, for example. In order to precipitate fine intermetallic compounds at a high density in such homogenization treatment at around 500°C, a long heat treatment is required, and a minimum of 6 hours is required. If the treatment is less than 6 hours, the precipitation is insufficient and the density of the fine intermetallic compounds may decrease. There is no upper limit on the homogenization treatment time, but from the viewpoint of production costs, it is preferable to keep it within 16 hours.

[0031] Hot rolling: Finishing temperature: 240℃ to 300℃ In hot rolling, it is desirable to set the finishing temperature to less than 300°C to suppress recrystallization. By setting the hot rolling finishing temperature to less than 300°C, the hot rolled sheet has a uniform fiber structure. If the hot rolling finishing temperature is 300°C or higher, recrystallization occurs in a part of the hot rolled sheet, resulting in a structure in which the fiber structure and the recrystallized structure are mixed, and there is a risk that the recrystallized grain size will become non-uniform during final annealing. If hot rolling is finished at less than 240°C, the temperature during hot rolling will be extremely low, so cracks will easily occur on the side of the rolled sheet, and there is a concern that productivity will be significantly reduced. Therefore, it is preferable that the finishing temperature of hot rolling is in the range of 240°C or higher and less than 300°C. There are no particular limitations on the finished sheet thickness, but in order to reduce the final cold rolling reduction ratio, it is preferable that the finished sheet thickness is 3.0 mm or more.

[0032] Final cold rolling ratio: 98% or more The higher the cold rolling reduction ratio from hot rolling to the final foil thickness, the greater the amount of strain accumulated in the material, resulting in finer recrystallized grains after final annealing. By performing cold rolling a required number of times at a required processing ratio and performing foil rolling, an aluminum alloy foil 1 having a thickness of about 10 μm to 0.2 mm, for example, a thickness of 40 μm, can be obtained. When cold rolling is performed a required number of times, it is preferable to perform the final foil rolling without intermediate annealing, and then perform final annealing. In addition, when final annealing is performed after cold rolling, the final annealing conditions are preferably such that the steel sheet is heated to 220° C. to 350° C. for about 30 minutes to 20 hours, and then slowly cooled.

[0033] The obtained aluminum alloy foil 1 contains a predetermined amount of Fe, which affects the texture of the aluminum alloy and contributes to refinement of the crystal grain size. Although the aluminum alloy contains 0.8 to 2.0 mass % of Fe, by performing foil rolling as the final cold rolling without intermediate annealing in the final stage of cold rolling and then final annealing, the aluminum alloy has good elongation even with the Fe content in the above range. The aluminum alloy used here may contain about 0.2 mass % or less of Si in addition to Fe. Even if the aluminum alloy foil 1 of this embodiment contains Si in the above range, an aluminum alloy foil that can achieve the purpose can be obtained.

[0034] By the manufacturing method described above, it is possible to obtain an aluminum alloy foil 1 having a maximum tensile strength of 85 MPa or more, a 0.2% yield strength of 45 MPa or more, and an elongation of 15% or more in a tensile test in a direction at 45° to the rolling direction, and having a ratio of the area ratio of Cu orientation to the area ratio of Cube orientation in the area ratios of each orientation on the surface (Cu orientation / Cube orientation) of 3 or more. The aluminum alloy foil 1 described above is suitable for food packaging or for use as a formed packaging material for lithium ion batteries, and can provide an aluminum alloy foil suitable for applications requiring large deformation by press forming, high elongation, and formability. In addition, since it can be produced without intermediate annealing after cold rolling, the aluminum alloy foil 1 can be obtained with excellent productivity. EXAMPLES

[0035] An aluminum alloy ingot having the composition shown in Tables 1 and 2 (the balance being Al and other unavoidable impurities) was produced by semi-continuous casting. The resulting ingot was then subjected to homogenization treatment, hot rolling, cold rolling, and final annealing under the manufacturing conditions shown in Tables 1 and 2 (homogenization treatment conditions, hot rolling finish temperature, hot rolling finish thickness, cold rolling finish foil thickness) to produce aluminum alloy foil. The conditions for final annealing were 300°C x 20 hours. The final thickness of the aluminum alloy foil was the thickness (foil thickness) shown in Tables 1 and 2. For samples that underwent intermediate annealing, intermediate annealing was performed under conditions of 360°C x 3 hours. In Tables 1 and 2, examples that were not subjected to intermediate annealing are marked with an "X" in the intermediate annealing column, and examples that were subjected to intermediate annealing are marked with an "O".

[0036] [Table 1]

[0037] [Table 2]

[0038] The obtained aluminum alloy foil was subjected to the following measurements and evaluations. Tensile strength (MPa), elongation (%) All of the measurements were performed using a tensile test. The tensile test was performed in accordance with JIS Z2241. A JIS No. 5 test piece was punched out of the aluminum alloy foil sample (using a Super Dumbbell (registered trademark) manufactured by Dumbbell Co., Ltd.) so that the elongation in the 45° direction relative to the rolling direction could be measured, and the tensile test was performed using a universal tensile tester (AGS-X 10kN manufactured by Shimadzu Corporation) at a tensile speed of 2mm / min. The elongation percentage was calculated as follows. First, before the test, two lines were marked perpendicular to the longitudinal center of the test piece at intervals of 50 mm, which is the gauge length. After the test, the fracture surfaces of the aluminum alloy foils were butted together to measure the distance between the marks, and the elongation amount (mm) obtained by subtracting the gauge length (50 mm) from the distance was divided by the gauge length (50 mm) to obtain the elongation percentage (%).

[0039] ·Azimuth area ratio Prior to crystal orientation analysis, the foil surface was mirror-finished by electrolytic polishing using a solution of perchloric acid:ethanol = 1:4 (volume ratio) at a voltage of 20 V for 5 seconds. After electrolytic polishing of the foil surface, crystal orientation analysis was performed using SEM (Scanning Electron Microscope)-EBSD, and the area ratio of each orientation was calculated. A FE-SEM (JSM-7900F manufactured by JEOL) was used for the SEM, and OIM Analysis (Ver.8.0) from TSL Solutions was used for the analysis. Deviation from the ideal orientation was limited to 15°.

[0040] The measurement conditions were as follows: observation magnification: 900x, acceleration voltage: 15kV, sample tilt angle: 70°, step size: 0.3μm. The observation area was a total of 50,000 μm2, obtained by combining images taken at 900x magnification. 2 The CI (Confidence Index) value was set to 0.1 or less, and a Minimum Grain Size [points] of 2 and Anti Grains of 2 were adopted.

[0041] (Azimuth analysis) The area ratio of each orientation was calculated using the Crystal Orientation function. The tolerance was set to less than 15°, and the Orientation Euler Angles and Orientation{hk(i)l}<uv(t)w> The area ratio was obtained by specifying as shown in Table 3 below. From the obtained area ratio, (Cu orientation area ratio / Cube orientation area ratio) was calculated to calculate the area ratio ratio.

[0042] [Table 3]

[0043] Rough surface In this example, the plastic working was performed by a tensile test. The tensile test was performed in the same manner as in the elongation measurement in the previous section, using a JIS No. 5 test piece and applying a tensile strain with the universal tensile tester. The surface roughness of the test material was measured based on JIS B0601:2001. The actual measurements were performed using a confocal laser microscope (Keyence, VK-X100) and an analysis application (Keyence, VK-H1XA) was used for analysis. The observation magnification was ×500, the field of view size was 1000 × 500 μm, and the measurement points were the center of the width and length of the JIS No. 5 test piece. The data scanned by the laser microscope was subjected to noise removal and tilt correction processing to measure the surface roughness. For noise removal, the noise detection level was set to [Normal], and for tilt correction, the correction method was selected to [Surface tilt correction (profile)]. The surface roughness parameter was calculated based on JIS B0601:2001 using the arithmetic mean roughness of the surface roughness. First, the surface quality of the test piece before the test is observed with a confocal laser microscope and this is designated as R0. Then, a tensile test is performed. The test is stopped midway when the strain during plastic deformation reaches 25%, and the surface quality of the test piece after plastic deformation is observed (surface roughness measurement) again at the same location as before the test, and this is designated as R 25 The same test piece was measured using the above procedure. 25 Using (R 25The test was carried out for the same level on n=5 or more levels, and the average value excluding the maximum and minimum values ​​was used as the calculated value of surface roughness.

[0044] ·Average grain size After electrolytic polishing of the foil surface, crystal orientation analysis was performed using SEM-EBSD, and crystal grains surrounded by grain boundaries with an inclination angle of more than 5° were analyzed using the Number method (number average crystal grain size) under the following conditions to calculate the average crystal grain size. The details of the analysis conditions are as follows. Grain Tolerance Angle: 5° Minimum Grain Size[points]:2 Anti Grains:2 Minimum Confidence Index: 0 Multiple rows required: All OFF Apply partition before calculation:OFF Include grains at edges of scan in statistics:OFF The average crystal grain size by the Number method is the diameter of a circle calculated by dividing the measurement area by the number of crystal grains. The measurement conditions are the same as for the orientation area ratio described above: observation magnification: 900 times, total area: 50,000 μm 2 It was decided.

[0045] ·LAGB length / HAGB length After electrolytic polishing of the foil surface, crystal orientation analysis was performed using SEM-EBSD to observe high-angle grain boundaries (HAGBs) with an orientation misorientation between crystal grains of 15° or more, and low-angle grain boundaries (LAGBs) with an orientation misorientation between 2° or more and less than 15°. Measurements were performed in three fields of view with a field size of 45 x 90 μm at a magnification of 900x, the lengths of the HAGBs and LAGBs within the field of view were obtained, and the ratio was calculated. The measurement conditions were the same as for the orientation area ratio described above, with observation magnification of 900x and a total area of ​​50,000 μm. 2 It was decided. In EBSD, by specifying the boundaries in the Grain-MAP, it is possible to perform analysis on grain boundaries with any orientation difference. Note that since there is a possibility that grain boundaries with an orientation difference of less than 2° contain noise, they were excluded from the calculation. In this application, the analysis was performed by specifying the orientation difference of 2° or more and less than 15° (=LAGB) as min:2°-max:15°, and the orientation difference of 15° or more (=HAGB) as min:15°(-max:90°), and the grain boundary length obtained by the analysis was used to calculate LAGB / HAGB.

[0046] Limit forming height The forming height was evaluated in a square tube forming test. The test was performed using a universal sheet metal forming tester (ERICHSEN Model 142 / 20) and a square punch (length of one side D = 37 mm, chamfered corner diameter R = 4.5 mm)2 with an aluminum foil of 40 μm thickness shown in Figure 2. The test conditions were as follows: wrinkle suppression force was 10 kN, the scale of the punch rise speed (forming speed) was 1, and mineral oil was applied as a lubricant to one side of the foil (the side that comes into contact with the punch). The aluminum alloy foil is pressed against the punch rising from the bottom of the device to form the foil, and the maximum punch height at which the foil can be formed without cracks or pinholes when it is pressed three times in succession is defined as the limit forming height (mm) of the aluminum alloy foil. The punch height was changed in 0.1 mm intervals. In this example, samples with a forming height of 11.0 mm or more were designated as excellent products by the symbol A, samples with a forming height of 10.0 mm or more and less than 11.0 mm were designated as acceptable products by the symbol B, and samples with a forming height of less than 10.0 mm were designated as unacceptable products by the symbol C.

[0047] Using the alloy compositions shown in Tables 1 and 2 and the manufacturing conditions shown in Tables 1 and 2, Examples No. 1 to 22 and Comparative Examples No. 23 to 31 were prepared. All of the Examples are examples that satisfy the desired compositions or manufacturing conditions described above. All of the Comparative Examples are examples that do not satisfy either the desired compositions or manufacturing conditions described above. For samples No. 1 to 31, the tensile strength (MPa) in the 0°, 45°, and 90° directions are shown in Tables 1 and 2. In addition, the yield strength (MPa) in the 0°, 45°, and 90° directions, the elongation (%) in the 0°, 45°, and 90° directions, the Cu orientation area ratio, the Cube orientation area ratio, and the area ratio ratio (Cu orientation area ratio / Cube orientation area ratio), the average crystal grain size (μm), and the surface roughness (ΔRa 25 The values ​​of -ΔRa0 (μm), (LAGB length / HAGB length), and limit forming height (mm) were obtained. The measurement results and evaluation are shown in Tables 4 and 5.

[0048] [Table 4]

[0049] [Table 5]

[0050] As shown in the results shown in Tables 1, 2, 4, and 5, the aluminum alloy foils made of an aluminum alloy containing 0.8% by mass or more and 2.0% by mass or less of Fe, 0.2% by mass or less of Si, with the remainder being Al and unavoidable impurities, had a maximum tensile strength of 85 MPa or more, a 0.2% proof stress of 45 MPa or more, and an elongation of 15% or more in a tensile test at 45° to the rolling direction, and had a ratio (Cu / Cube) of the area ratio of Cu orientation to the area ratio of Cube orientation in the area ratio of each orientation on the surface of 3 or more, and had small surface roughness and excellent limit forming height. Moreover, the samples of these examples have an average crystal grain size of 4 μm or less, which is sufficiently small. Furthermore, the samples of these examples have a low surface roughness (Ra 25 -Ra0) is 0.30 μm or less, which is sufficiently small.

[0051] The Fe content of the example sample is 0.82% or more and 1.96% or less, and the Si content is 0.03% or more and 0.19% or less. The foil thickness of the example sample is 25 μm or more and 80 μm or less. The maximum tensile strength of the example sample in a tensile test in a 45° direction to the rolling direction is 86 MPa or more and 101 MPa or less. The 0.2% proof stress in a 45° direction to the rolling direction is 48 MPa or more and 74 MPa or less. The Cu orientation / Cube orientation value of the example sample is 5.8 or more and 30.8 or less. The average crystal grain size of the example sample is 2.53 μm or more and 3.42 μm or less. The surface roughness of the example sample is 0.17 μm or more and 0.29 μm or less. The LAGB / HAGB value of the example sample is 0.52 or more and 0.88 or less. The limit forming height of the example sample is 10.1 mm or more and 12.5 mm or less.

[0052] In contrast to these examples, samples No. 23 and No. 24 had Fe contents outside the above range, but they had lower tensile strength, lower yield strength, and lower elongation than the example samples in the same direction. They also had a tendency to have large surface roughness and a lower limit forming height. The samples No. 25 and No. 26, which have a Si content outside the above range, have lower tensile strength, lower proof stress, and lower elongation than the example samples in the same direction. In addition, the limit forming height is also lower. Samples No. 27, 28, and 29 were samples that underwent intermediate annealing, but had lower tensile strength, lower yield strength, and lower elongation in the same direction than the samples of the embodiment. Also, compared to the samples of the embodiment, samples No. 27 to 29 had larger average crystal grain size, greater surface roughness, smaller (LAGB / HAGB) values, and lower limit forming height.

[0053] Sample No. 30 was a sample in which the homogenization temperature was higher than the desired range, but it had low yield strength, a slightly larger average crystal grain size than the example samples, slightly larger surface roughness, and a worsened limit forming height. Sample No. 31 was a sample in which the homogenization temperature was lower than the desired range, but the average crystal grain size was slightly larger than those of the example samples, the surface roughness was slightly larger, and the limit forming height was worse than that of the example samples. [Explanation of symbols]

[0054] 1...aluminum alloy foil, 2...punch.

Claims

1. An aluminum alloy foil made of an aluminum alloy containing Fe: 0.8% by mass or more and 2.0% by mass or less, Si: 0.2% by mass or less, with the remainder being Al and unavoidable impurities, the aluminum alloy foil having a 0.2% proof stress of 45 MPa or more, an elongation of 15% or more, and a ratio of an area ratio of Cu orientation to an area ratio of Cube orientation in the area ratios of each orientation on a surface (Cu orientation / Cube orientation) of 3 or more, On the surface, the average crystal grain size of crystal grains surrounded by an orientation difference of 5° or more is 3.5 μm or less; An aluminum alloy foil, characterized in that a ratio of grain boundary lengths in the same field of view obtained by performing crystal orientation analysis by an EBSD method on a surface of the foil satisfies the following formula (1): Length of grain boundaries of crystal grains with orientation difference of 2° or more and less than 15° / Length of grain boundaries of crystal grains with orientation difference of 15° or more>0.5... (1)

2. The aluminum alloy foil according to claim 1, characterized in that, instead of the formula (1), the ratio of grain boundary lengths in the same field of view obtained by performing crystal orientation analysis on the surface by an EBSD method satisfies the following formula (2). 0.52≦grain boundary length of crystal grains with orientation difference of 2° or more and less than 15° / grain boundary length of crystal grains with orientation difference of 15° or more≦0.88 (2)

3. Initial surface roughness Ra 0 and the surface roughness Ra at 25% strain in the tensile test 25 The difference between the surface roughness (Ra 25 -Ra 0 3. The aluminum alloy foil according to claim 1, wherein the thickness of the aluminum alloy foil is 0.30 μm or less.

4. An aluminum alloy foil made of an aluminum alloy containing Fe: 0.8% by mass or more and 2.0% by mass or less, Si: 0.2% by mass or less, with the remainder being Al and unavoidable impurities, the aluminum alloy foil having a 0.2% proof stress of 45 MPa or more, an elongation of 15% or more, and a ratio of an area ratio of Cu orientation to an area ratio of Cube orientation in the area ratios of each orientation on a surface (Cu orientation / Cube orientation) of 3 or more, On the surface, the average crystal grain size of crystal grains surrounded by an orientation difference of 5° or more is 3.5 μm or less; Initial surface roughness Ra 0 and the surface roughness Ra at 25% strain in the tensile test 25 The difference between the surface roughness (Ra 25 -Ra 0 ) is 0.30 μm or less.

5. The surface roughness (Ra 25 -Ra 0 5. The aluminum alloy foil according to claim 4, wherein the average grain size is 0.17 μm or more and 0.29 μm or less.

6. The aluminum alloy foil is made of an aluminum alloy containing 0.8% by mass or more and 2.0% by mass or less of Fe, 0.2% by mass or less of Si, with the remainder being Al and unavoidable impurities, and is characterized in that the aluminum alloy foil has a 0.2% proof stress of 45 MPa or more, an elongation of 15% or more, a ratio of an area ratio of Cu orientation to an area ratio of Cube orientation in the area ratios of each orientation on the surface (Cu orientation / Cube orientation) of 3 or more, an average crystal grain size of crystal grains surrounded by an orientation difference of 5° or more on the surface of 3.5 μm or less, and a ratio of crystal grain boundary lengths in the same field of view on the surface obtained by performing crystal orientation analysis by an EBSD method satisfies the following formula (1): A method for producing an aluminum alloy foil, comprising the steps of: subjecting an ingot of an aluminum alloy having the above composition to a homogenization treatment in which the ingot is heated and held at 480 to 540°C for 8 hours or more and then cooled; subjecting the ingot to hot rolling with a finishing temperature of 240°C or more and less than 300°C; subjecting the ingot to cold rolling with a rolling reduction rate of 98% or more; thereafter, foil rolling without intermediate annealing; and subjecting the ingot to final annealing in which the ingot is heated to 220 to 350°C for 30 minutes to 20 hours. Length of grain boundaries of crystal grains with orientation difference of 2° or more and less than 15° / Length of grain boundaries of crystal grains with orientation difference of 15° or more>0.5... (1)

7. The method for producing an aluminum alloy foil according to claim 6, characterized in that an aluminum alloy foil is produced in which a ratio of grain boundary lengths in the same field of view obtained by performing crystal orientation analysis on a surface by an EBSD method satisfies the following formula (2) instead of the formula (1). 0.52≦grain boundary length of crystal grains with orientation difference of 2° or more and less than 15° / grain boundary length of crystal grains with orientation difference of 15° or more≦0.88 (2)

8. Initial surface roughness Ra 0 and the surface roughness Ra at 25% strain in the tensile test 25 The difference between the surface roughness (Ra 25 -Ra 0 8. The method for producing an aluminum alloy foil according to claim 6, wherein the thickness of the aluminum alloy foil is 0.30 μm or less.

9. The aluminum alloy foil is made of an aluminum alloy containing 0.8% by mass or more and 2.0% by mass or less of Fe, 0.2% by mass or less of Si, and the remainder being Al and unavoidable impurities, and has a 0.2% proof stress of 45 MPa or more, an elongation of 15% or more, a ratio of an area rate of Cu orientation to an area rate of Cube orientation in the area rate of each orientation on the surface (Cu orientation / Cube orientation) of 3 or more, an average crystal grain size of crystal grains surrounded by an orientation difference of 5° or more on the surface is 3.5 μm or less, and an initial surface roughness Ra 0 and the surface roughness Ra at 25% strain in the tensile test 25 The difference between the surface roughness (Ra 25 -Ra 0 ) is 0.30 μm or less, A method for producing an aluminum alloy foil, comprising the steps of: subjecting an ingot of an aluminum alloy having the above composition to a homogenization treatment in which the ingot is heated and held at 480 to 540°C for 8 hours or more and then cooled; subjecting the ingot to hot rolling with a finishing temperature of 240°C or more and less than 300°C; subjecting the ingot to cold rolling with a rolling reduction rate of 98% or more; thereafter, foil rolling without intermediate annealing; and subjecting the ingot to final annealing in which the ingot is heated to 220 to 350°C for 30 minutes to 20 hours.

10. The surface roughness (Ra 25 -Ra 0 10. The method for producing an aluminum alloy foil according to claim 9, wherein the aluminum alloy foil has a grain size of 0.17 μm or more and 0.29 μm or less.

11. The method for producing an aluminum alloy foil according to any one of claims 6, 7, 9, and 10, characterized in that the homogenization treatment is carried out under conditions of heating and holding at 480 to 540 ° C. for 8 hours to 16 hours and then cooling.

12. The method for producing an aluminum alloy foil according to claim 8, characterized in that the homogenization treatment is carried out under conditions of heating and holding at 480 to 540°C for 8 hours to 16 hours, and then cooling.

Citation Information

Patent Citations

  • Production of aluminum foil having excellent strength and workability

    JP1988020103A

  • Material for aluminum alloy foil and production method of the same

    JP2002038234A

  • Aluminum alloy foil, method of producing the same, and aluminum layered product

    JP2004027353A

  • Aluminum alloy foil for electrode collector

    JP2018168450A

  • Aluminum alloy foil and manufacturing method of aluminum alloy foil

    JP2019014939A

Cited By

  • Aluminum alloy foil and method for producing same

    JP2025166259A

  • Aluminum alloy foil and method for manufacturing the same

    JP7923876B2